A comparison of the sealing ability of various temporary restorative materials to seal the access cavity: An in vitro study - Aji Markose; Ramesh Krishnan; Maya Ramesh; Shishir Singh (Wolters Kluwer Medknow Publications, 2016)
Introduction: In multiple-appointment root canal treatment, a temporary filling material is used to seal the access cavity between visits. The primary function of this material is to prevent the contamination of the root canal system by fluids, organic debris, and bacteria from the oral cavity. Material and Methods: A total of fifty extracted noncarious unrestored human maxillaryanterior teeth with intact crowns and roots were selected The canals were instrumented using stepback technique and sodium hypochlorite (3%) and hydrogen peroxide (3%) were used as irrigants for each specimen alternatively. The coronal two-thirds of each canal were flared using Gates-Glidden drills up to no. 3 size and obturated with Gutta-percha using zinc oxide-eugenol (ZnOE) as sealer. The teeth were then randomly selected and divided into six groups out of which four were experimental groups and two control groups. The teeth were then immersed in 2% methylene blue dye solution for 3 days. All sealing materials and Gutta-percha were gently removed from the walls of the canal, and the entire circumference of the canal wall examined for dye penetration. Results: The lowest mean leakage was in the Fermit-N group followed by Cavit-W, ZnOE, intermediate restorative materials (IRM), and positive control. Conclusion: Fermit-N showed better sealing ability compared to cavit, ZnOE and IRM.